Procedural Fairness in Budgeting and Employee Performance in The Context of Information Sharing - Evelyn Stefanie Wangsa; SeTin SeTin (Journal of Governance Risk Management Compliance and Sustainability, 2024)
Information sharing and procedural fairness are crucial for achieving business objectives through employee performance. The results of this research will help firm management make decisions about how to improve employee and company performance by upholding procedural fairness and increasing information sharing between superiors and subordinates. This research aims to examine the effect of procedural fairness on information sharing, the effect of information sharing on employee performance, and the mediating role of information sharing on the effect of procedural justice on employee performance. This study uses primary data collected through questionnaires. The sample consisted of 108 sub-manager level employees (services, trade, and manufacturing) selected based on a purposive sampling technique. Data analysis was conducted using the regression method. Data analysis findings indicate that procedural fairness affects employee performance, which is mediated by information sharing. If procedural justice is applied, communication will be better, especially regarding relevant information; this can improve employee . As demonstrated by empirical studies of Indonesian companies, there is currently no research that reveals the relationship between procedural fairness, information sharing, and employee performance. performance. However, cross-sectional studies have flaws because they frequently lack evidence of causal links between the variables they study. According to empirical studies on Indonesian organizations, no research has demonstrated a connection between procedural fairness, information sharing, and employee performance. Based on the results of the data analysis, it can be concluded that procedural fairness and information sharing positively related to employee performance.